Effect of curing temperature on the reaction kinetics of cementitious steel slag-fly ash-desulfurized gypsum composites system. (15th December 2022) - Duan, Siyu; Wu, Hao; Zhang, Ke; Liao, Hongqiang; Ma, Zhibin; Cheng, Fangqin
Abstract: Solid waste-based binders have been widely studied for decades. Recently, the steel slag-fly ash-desulfurized gypsum (SS-FA-DG) composite system was developed as a novel building cementitious material, however, its reaction mechanism and reaction process mains unclear. This paper investigated the reaction kinetics of SS-FA-DG composite system by evaluating the influence of curing temperature on the formation of hydration products and the development of mechanical properties. The pH of the SS-FA-DG slurry was measured by the online pH meter. The compressive strength, chemical bonding, mineral composition, and degree of hydration of cementitious SS-FA-DG blocks over a curing period of 28 days were evaluated using compression tests, Fourier transform infrared spectroscopy, X-ray diffraction and thermogravimetric analyses, respectively. The results indicate that the SS-FA-DG composite system was found to develop via a five-stage process: dissolution of steel slag (I) and fly ash (Ⅱ), formation of hydration products such as calcium silicate hydrate gels (C–S–H) and ettringite (AFt) crystallite (Ⅲ), nucleation and crystallization of hydration products (Ⅳ), and growth and diffusion (Ⅴ). The compressive strength was largely governed by the development of the hydration reaction, which is influenced by the curing temperature. The reaction time of each stage was shortened at elevated curing temperatures, thereby increasing the compressive strength of the material more quickly. Highlights: The cementitious SS-FA-DG block was prepared by compression molding technology. The reaction mechanism and reaction process of SS-FA-DG are investigated. The hydration reaction of SS-FA-DG composite system can be divided into five stages.